Hermeticity of Electronic Packages (2nd Edition) - Greenhouse, Hal (Elsevier, 2012)
This is a book about the integrity of sealed packages to resist foreign gases and liquids penetrating the seal or an opening (crack) in the package, especially critical to the reliability and longevity of electronics. The author explains how to predict the reliability and the longevity of the packages based on leak rate measurements and the assumptions of impurities. Non-specialists in particular will benefit from the author's long involvement in the technology. Hermeticity is a subject that demands practical experience, and solving one problem does not necessarily give one the background to solve another. Thus, the book provides a ready reference to help deal with day to day issues as they arise. The book gathers in a single volume a great many issues previously available only in journals or only in the experience of working engineers. How to define the "goodness" of a seal? How is that seal measured? How does the integrity of the seal affect circuit reliability? What is the significance of the measured integrity of the seal? What is the relationship of Residual Gas Analysis and the seal integrity? The handbook answers these questions and more, providing an analysis of nearly 100 problems representative of the wide variety of challenges that actually occur in industry today.